40.2k views
2 votes
Solve the following linear quadratic system of equations algebraically.

y=^2+3x-2
y+3=5x

User Mchacki
by
6.4k points

1 Answer

3 votes

Answer:


x=1


y=2

Explanation:


y=x^2+3x-2 ,
y+3=5x

Replace all occurrences of
y in
y+3=5x with
x^2+3x-2.


(x^2+3x-2)+3=5x


y=x^2+3x-2

Add
-2 and 3.


x^2+3x+1=5x


y=x^2+3x-2

Subtract 5x from both sides of the equation.


x^2+3x+1-5x=0


y=x^2+3x-2

Subtract 5x from 3x.


x^2-2x+1=0


y=x^2+3x-2

Rewrite 1 as
1^2.


x^2-2x+1^2=0


y=x^2+3x-2

Check that the middle term is two times the product of the numbers being squared in the first term and third term.


2x=2 ·
x ·
1


y=x^2+3x-2

Rewrite the polynomial.


x^2-2 ·
x ·
1
+
1^2=0


y=x^2+3x-2

Factor using the perfect square

trinomial rule
a^2-2ab+b^2=(a-b)^2,

where a = x and b = 1.


(x-1)^2=0


y=x^2+3x-2

Set the
x-1 equal to 0.


x-1=0


y=x^2+3x-2

Add 1 to both sides of the equation.


x=1


y=x^2+3x-2

Replace all occurrences of
x in


y=x^2+3x-2 with 1.


y=(1)^2+3(1)-2


x=1


y=2

User Mynawaz
by
5.9k points